vereniging voor archeologische experimenten en educatie (2000)
[Dt.:] Die Gesellschaft für Archäologische Experimente und Lehre ist eine Niederländische Plattform für alle, die sich mit diesem Bereich beschäftigen. Unter den Mitgliedern sind Museen, Universitäten und Einzelpersonen die experimentelle Archäologie praktizieren und für die Lehre verwenden. Auf der Web Site findet man jede Menge Informationen über Aktivitäten und Projekte, wie auch Photos, Publikationen und das "Bulletin for Archaeological Experiments and Education" (BAEE). - [Engl.:] The Association for Archaeological Experiments and Education is the Dutch National platform for all those interested in archaeological experiments and education. Among the members, there are archaeological (open air)museums, universities, as well as individuals professionally practicing experimental archaeology and / or archaeological education. The web site covers lots of information about activites and projects as well as photos, publications, contact information and the "Bulletin for Archaeological Experiments and Education" (BAEE).